2016
DOI: 10.1074/jbc.m115.695320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Unique Pathway for 4-Cresol Catabolism Initiated by Phosphorylation in Corynebacterium glutamicum

Abstract: 4-Cresol is not only a significant synthetic intermediate for production of many aromatic chemicals, but also a priority environmental pollutant because of its toxicity to higher organisms. In our previous studies, a gene cluster implicated to be involved in 4-cresol catabolism, creCDEFGHIR, was identified in Corynebacterium glutamicum and partially characterized in vivo. In this work, we report on the discovery of a novel 4-cresol biodegradation pathway that employs phosphorylated intermediates. This unique p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Thus it seems that while CYP114 is catalytically capable of the full transformation of 4 to 7 , SDR GA is necessary for the efficient oxidation of 6 to 7 to occur. The use of a dehydrogenase for this type of chemical transformation is not uncommon, as it has been shown in biosynthetic pathways for other metabolites that the relevant CYPs do not efficiently catalyze full oxidation to the carboxylate, leading to a requirement for alcohol and/or aldehyde dehydrogenases for complete conversion 3032 . However, neither plant nor fungal GA biosynthesis rely on a dedicated dehydrogenase 1 , and therefore this enzyme is unique to the bacterial pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it seems that while CYP114 is catalytically capable of the full transformation of 4 to 7 , SDR GA is necessary for the efficient oxidation of 6 to 7 to occur. The use of a dehydrogenase for this type of chemical transformation is not uncommon, as it has been shown in biosynthetic pathways for other metabolites that the relevant CYPs do not efficiently catalyze full oxidation to the carboxylate, leading to a requirement for alcohol and/or aldehyde dehydrogenases for complete conversion 3032 . However, neither plant nor fungal GA biosynthesis rely on a dedicated dehydrogenase 1 , and therefore this enzyme is unique to the bacterial pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The P450 enzyme CreJ (also named CYP288A2 by Nelson et al) (31) catalyzes the successive oxidations from 1′→1′a→1′b→1′c in the presence of redox partners CreE and CreF, and the electron donor NADPH (30). Although different oxidative modifications of the distal methyl group are well tolerated by CreJ, the tethered phosphate group is required for the activity of this P450 enzyme because the nonphosphorylated substrate cannot be recognized (30). To understand this unique substrate recognition mechanism, the X-ray crystal structure of CreJ in complex with 1′ was solved at 2.0 Å (PDB ID code: 5GWE).…”
Section: Resultsmentioning
confidence: 99%
“…2A) in the Gram-positive bacterium Corynebacterium glutamicum (30). Initially, 1 is phosphorylated to 1′ by a novel 4-methylphenyl phosphate synthase, CreHI, with consumption of ATP.…”
mentioning
confidence: 99%
“…Such enzymes were discovered also in Rhodococcus. Other studies have shown that cytochromes can oxidize both linear alkanes and aromatic hydrocarbons (Bell & Wong, 2007;Du et al, 2006;Ignatovets, Akhramovich, & Leontiev, 2009).…”
Section: Significant Differences Inmentioning
confidence: 99%